Síndrome de Dandy-walker The Dandy-Walker syndrome. Report of four cases - Jaderson Costa da Costa; Adão Anicet; Mario Ferreira Coutinho (Arquivos de Neuro-Psiquiatria)
São relatados os casos de 4 pacientes com síndrome de Dandy-Walker diagnosticada pela pneumencefalografia fracionada e ventriculografia. O tratamento e a patogenia desta malformação são discutidos com base em dados embriológicos. Four cases of Dandy-Walker syndrome diagnosed through encephalography and ventriculography with air are reported. The pathogenesis of this malformation is discussed. Particularly stressed are the radiological aspects of the condition, which are considered to be pathognomonic. The roentgenological findings are quite typical, indicating the extreme dolichocephaly, thinning and bulging of the bones of the posterior cranial fossa, prominent separation of the lambdoid sutures and an abnormal position of the lateral sinuses. Ventriculography shows symmetric hydrocephalus with extremely large cyst -like formation in the posterior fossa. Surgical indications are also considered. The ventricle lateral shunt is the recommended treatment for the DandyWalker malformations which show cerebral subarachnoid agenesis by pneumoencephalography.